(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article talks about the meaning of the words “night” and “morning” in the modern Uzbek language. It is explained that these two concepts have different meanings and tasks in linguistics and literature, and that they have their own meanings not only in these two sciences, but also in concrete and natural sciences. The fact that night and morning have different meanings and expressive tasks in literature is explained on the basis of examples.